Pengaruh Penggunaan Beberapa Jenis Ekstrak Tanaman Beralkaloid terhadap Produk Teh Kombucha - Yulia M. Nur; Sri Indrayati; Periadnadi Periadnadi; Nurmiati Nurmiati (Jurnal Biologi Universitas Andalas, 2018)
The research about The Effect of Some Alkaloid’s Plant Extract as Activator and the plant media for Acetobacter xylinum (Brown.) Holland in  Fermented of Kombucha Tea, has been done from February to September in STIKes Perintis Laboratory. The aim of this study to know the effects of some alkaloid’s plant extract as activator and the plant media for Acetobacter xylinum (Brown.) Holland in  Fermented of Kombucha Tea. The research used Completely Random Design (CRD) with 6 treatments and 4 replications. The treatments were : black tea, green tea, leaf of coffea, leaf of cocoa, coffea powder and cocoa powder. The result showed that the use of several types of plant extract beralkaloid effect on Kombucha tea products. In this study obtained the average of the highest total bacteria Acetobacter xylinum 117.50 x 107 cfu / ml, the value of pH 3.82, sugar content 9.67. The results of the organoleptic assessment of flavor and taste showed the highest panelist favorites level in Kombucha chocolate powder that is 3.07 (very good) and 3.47 (very good).